Formación en escritura profesional y académica. Representaciones sobre géneros profesionales de la crítica de arte, la curaduría y sobre géneros académicos de titulación en UNA - Proyecto - Di Stéfano, Mariana (2015)
This research aims at analyzing discourses of curators and arts critics professional studies. The aim is to go on describing genres repertoires which are central in professional practices. The team intends to precise information to design the didactic strategies in the writing workshops of the PREU, the graduate and posgraduate courses of the Art Criticism Area. Also as a continuation of the previous project, this one intends to identify students’ social representations on art criticism, curatorship and the genres related, since we consider necessary to intervene in a didactic way on the representations students have when they start studies in the area. The present investigation opens another object of inquiry, the description of genres connected to knowledge production and graduating at UNA (dissertations, thesis, curatorial projects). The purpose is to identify UNA community’s representations on these genres which students must produce to graduate and to develop abilities to create new knowledge, abilities often demanded in critics and curators tasks. We consider it very relevant because of the difficulties implied in the elaboration of this sort of writings, which are one of the main reasons why most students do not graduate at postgraduate careers in the country.